(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Riflessioni a margine della libertà religiosa con specifico riguardo alle confessioni senza rappresentanza - 2. I disegni di legge sulla libertà religiosa e i rapporti con le confessioni non strutturate o prive di adeguata rappresentanza istituzionale - 3. Le confessioni religiose senza rappresentanza: ulteriori osservazioni e prospettive. Remarks on religions lacking any adequate institutional representatives in the light of social-ethnic context ABSTRACT: Because of intense migratory flows today, the coexistence of various religious movement, often very different among them, in our society has increased. This phenomenon is known as ‘religious pluralism’ and it implies that before the law all religions have the right to exist, to preach their own doctrines, to worship, and to gain a recognition of ‘special’ juridical positions. In this background the religious factor is a diriment element and represents the focal point of cultural and juridical debate.